1985
DOI: 10.4141/cjas85-099
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Acclimation to High Nitrate Intakes on Some Rumen Fermentation Parameters in Sheep

Abstract: . 1985. Effect of acclimation to high nitrate intakes on some rumen fermentation parameters in sheep. Can. J. Anim. Sci. 65:841-849.Four sheep, fed a basal diet which included 44o/o cereal grain and 50Vo hay and which was supplemented with KNOr, were progressively acclimated to a KNO. intake of 2.5 g.kg body wt ''day-'. Nitrate and nitrite reducing activity in strained rumen fluid (SRF) collected 2 h after feeding showed maximum values of 45.3 p"g N'mL r'h land 39.4 pg N'mL ''h ', respectively, at an int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
1

Year Published

1988
1988
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 21 publications
(1 reference statement)
5
40
1
Order By: Relevance
“…Allison and Reddy (1984) found increased nitrate and nitrite reduction activities by rumen bacteria in vitro after an acclimation. Alaboudi and Jones (1985) also reported from two in vitro experiments that when sheep were acclimated to nitrate (from 0.5 g nitrate kg (1 BW to 2.5 g kg (1 BW over 2 wk), ruminal nitrate and nitrite reduction capacities were increased up to fivefold and the population of nitrate-reducing bacteria was three times greater. Recently, Shi et al (2012) confirmed that the nitrate reduction rate was greater when rumen fluid was used from sheep acclimated to nitrate compared with fluid from sheep not acclimated to nitrate.…”
Section: Figmentioning
confidence: 71%
“…Allison and Reddy (1984) found increased nitrate and nitrite reduction activities by rumen bacteria in vitro after an acclimation. Alaboudi and Jones (1985) also reported from two in vitro experiments that when sheep were acclimated to nitrate (from 0.5 g nitrate kg (1 BW to 2.5 g kg (1 BW over 2 wk), ruminal nitrate and nitrite reduction capacities were increased up to fivefold and the population of nitrate-reducing bacteria was three times greater. Recently, Shi et al (2012) confirmed that the nitrate reduction rate was greater when rumen fluid was used from sheep acclimated to nitrate compared with fluid from sheep not acclimated to nitrate.…”
Section: Figmentioning
confidence: 71%
“…Essentially, the NRB and SRB must be concentrated in the biofilm matrix to outcompete the methanogens. The SRB and NRB occur naturally in the rumen (Coleman 1960;Hungate 1966;Howard and Hungate 1976;Cheng et al 1988;Leng 2008) and experiments with sheep and cattle indicate that the population density of these species increases as the concentration of their respective electron acceptors in the ruminant diet increases (Alaboudi and Jones 1985;Hao et al 2009). Which microbial species is the most successful in using the particular oxidised substrate (HCO 3 -, nitrate or sulfate) depends on the distance between the colonies of the organism involved in the interspecies transfer, the partial pressure of H 2 and the Gibbs free-energy change of the reaction.…”
Section: Interspecies H 2 Transfermentioning
confidence: 99%
“…When nitrate replaced urea in the rumen, there was also a tendency for an increased microbial cell yield (cells also represent an electron sink) (Nolan et al 2010). Increased acetate relative to propionate production may result from a channelling of more carbohydrate through pyruvate and acetyl CoA in the fermentative pathways, or it could be a result of acetogenic oxidation of butyrate and propionate by the boosted nitratereducing capacity of rumen contents and increased populations of NRB (Alaboudi and Jones 1985) and SRB. The latter, from animal and human large intestine, have been shown to oxidise propionate and butyrate to acetate (Gibson 1990).…”
Section: The Ruminal Effects Of Promoting Nrb And/or Srb By Supplemenmentioning
confidence: 99%
“…When nitrate is drenched at high concentration, there is no accumulation of nitrate in the rumen, it is absorbed by the rumen, a part of it is excreted and a part is recycled through saliva (Wang et al 1961 ). This absorption of nitrate through the rumen will be drastically reduced if the animals are adapted to higher concentration of nitrate in the diet (Alaboudi and Jones 1985 ). The adaptation of the animals increases its ability to use nitrate and nitrite more effi ciently in the rumen, and these are metabolized effi ciently into the body tissue.…”
Section: Adaptation Of Ruminants To High Nitrate Dietsmentioning
confidence: 99%
“…The in vitro results at IVRI, Izatnagar, indicate that an inoculum of nitrate-/ nitrite-reducing bacteria can be an alternative to periodic and slow adaptation for obtaining similar results with nitrate utilizing capacity of the animals. It is very interesting to note that adapted animals return to normal level of its capability to use nitrate in diet within 3 weeks once the nitrate is withdrawn from the ration of sheep (Alaboudi and Jones 1985 ).…”
Section: Adaptation Of Ruminants To High Nitrate Dietsmentioning
confidence: 99%